Biology and insights into the role of cohesin protease separase in human malignancies. (8th February 2017) - Zhang, Nenggang; Pati, Debananda
ABSTRACT: Separase, an enzyme that resolves sister chromatid cohesion during the metaphase‐to‐anaphase transition, plays a pivotal role in chromosomal segregation and cell division. Separase protein, encoded by the extra spindle pole bodies like 1 ( ESPL1 ) gene, is overexpressed in numerous human cancers including breast, bone, brain, and prostate. Separase is oncogenic, and its overexpression is sufficient to induce mammary tumours in mice. Either acute or chronic overexpression of separase in mouse mammary glands leads to aneuploidy and tumorigenesis, and inhibition of separase enzymatic activity decreases the growth of human breast tumour xenografts in mice. This review focuses on the biology of and insights into the molecular mechanisms of separase as an oncogene, and its significance and implications for human cancers.